Bibliometric Analysis Of Academic Production in The Field of Media Economics and Management: A Wos-Based Study - Eşidir, Osman Vedüd; Bak, Gökhan; Altıntop, Mevlüt; Karadağ, Bedriye (Fenerbahçe University, 2025)
This study examines the development dynamics of academic production in the field of media economics and management using bibliometric analysis. A comprehensive search in the Web of Science (WoS) database, based on selected keywords, identified 1,035 academic studies, which were analyzed in terms of publication year, citation count, author collaborations, publication languages, affiliated institutions, and WoS index categories. The findings reveal a significant increase in publication and citation numbers, particularly after 2010, indicating a growing global academic interest. Countries such as the USA, Germany, the UK, and Spain lead in scientific contributions, with English-language publications being predominant. The study also highlights the limited academic contribution from Turkey, with low citation counts for Turkish-language publications. Citation analyses indicate that certain authors and universities play a central role in shaping academic production in media economics. The most cited studies focus on fundamental principles of media economics, advertising, media management, and digitalization. Bibliometric analyses further demonstrate that the field exhibits an interdisciplinary structure, with strong interactions between media, economics, and business. This study provides valuable insights into how academic production in media economics and management has evolved over time, identifying key research areas and future research trends. The findings emphasize that digitalization and emerging media platforms are among the key drivers shaping academic production in the field.

Bu çalışma, medya ekonomisi ve işletmeciliği alanındaki akademik üretimin gelişim dinamiklerini bibliyometrik analiz yöntemiyle incelemektedir. Web of Science (WoS) veri tabanında belirlenen anahtar kelimelerle gerçekleştirilen kapsamlı tarama sonucunda 1035 akademik çalışma tespit edilmiş ve bu çalışmalar yayın yılı, atıf sayısı, yazar iş birlikleri, yayın dilleri, yayımlayan kurumlar ve WoS indeks kategorileri gibi değişkenler temelinde analiz edilmiştir. Bulgular, özellikle 2010 sonrası dönemde yayın ve atıf sayılarında belirgin bir artış olduğunu ve akademik ilginin küresel ölçekte yoğunlaştığını göstermektedir. ABD, Almanya, İngiltere ve İspanya gibi ülkelerin yüksek sayıda yayın üreterek alandaki bilimsel yönelimi belirlediği, İngilizce yayınların ise baskın olduğu görülmüştür. Türkiye’den yapılan akademik katkının sınırlı olduğu ve Türkçe yayınlara yapılan atıfların düşük seviyede kaldığı belirlenmiştir. Atıf analizleri, belirli yazarların ve üniversitelerin medya ekonomisi alanındaki akademik üretimde merkezi konumda olduğunu ortaya koymaktadır. En fazla atıf alan çalışmaların medya ekonomisinin temel prensipleri, reklam, medya yönetimi ve dijitalleşme gibi konulara odaklandığı görülmüştür. Bibliyometrik analizler, alanın disiplinler arası bir yapı sergilediğini ve medya, ekonomi ve işletme alanlarıyla güçlü etkileşim içinde olduğunu göstermektedir. Çalışma, medya ekonomisi ve işletmeciliği alanındaki akademik üretimin zaman içinde nasıl şekillendiğini, hangi araştırma alanlarının öne çıktığını ve gelecekteki araştırmalara yön verebilecek eğilimleri belirleyerek alana önemli katkılar sunmaktadır. Bulgular, dijitalleşme ve yeni medya platformlarının akademik üretimi yönlendiren temel dinamikler arasında yer aldığını ortaya koymaktadır.
Medya Ekonomisi ve İşletmeciliği Alanında Akademik Üretimin Bibliyometrik Analizi: Wos Tabanlı Bir Araştırma
Keywords: Communication and Media Studies (Other); İletişim ve Medya Çalışmaları (Diğer); Econometrics (Other); Ekonometri (Diğer)